"We Fervently Pray": Reading Afro-Protestant Prayer as Genre Intervention in "The Petition of Absalom Jones and Others—People of Colour and Freemen of Philadelphia" - Sanders, Jorden E. (Christianity & literature, 2024)
While scholars have long documented Christianity’s influence on African American literature and print, few have investigated how specific Afro-Protestant practices inform alternative modes of collective action and writing in the early American republic. This essay follows scholarship’s recent turn by reading Afro-Protestant prayer within discourses of civic and religious petition at the turn of the nineteenth century. Sanders contends that early African American advocates mobilized prayer’s genre flexibility in their public addresses to challenge America’s growing antagonism toward antislavery petitions. These early theorizations of Afro-Protestant prayer as petitionary activism reframe how we understand a tradition of circulated prayers from nineteenth-century print to the present.